Clinical Observations of Golden Seachers (Stichopus Variegatus) and Acupuncture in Diabetes Mellitus Patients - Ang, Suryawan; Sugiarto, Maria Theresia Vera Ernawati (Budapest International Research and Critics University, 2021)
Indonesia is the largest archipelagic country in the world which has 17,504 islands with a coastline length of 81,000 km with an area of marine waters of about 5.8 million km2 (75% of the total area of Indonesia), stretching on the equator, causing Indonesia to have abundant biological resources. rich and diverse both for land and sea areas, so it is known as a mega biodiversity country (Karnila, 2020). This biological wealth needs to be utilized as well as possible for the welfare of the Indonesian people. One of the marine products that have important economic value is sea cucumber or also called sea cucumber, teat fish and sea ginseng. This type of research is quantitative research using a quantitative design with experimental research with aapproach quasi-pretest-posttest control design. There was a decrease in blood sugar levels and symptoms of diabetes in diabetic patients during 4 weeks of therapy, who were given gold sea cucumber treatment therapy and acupuncture as an alternative treatment.